Teorijski pristup definiranju nekonvencionalnih prijevoznih tehnologija s valorizacijom sredstava zračnog prometa - Steiner, Sanja (Promet - Traffic&Transportation, 2012)
The paper deals with a theoretical analysis of the problem of non-uniform defining of a group of non-conventional transport technologies. In this some basic approaches have been differentiated of various defining criteria, engineering/ technological and legal. In a comparative analysis of specific systems of air transport the author deals with the assessment of the possibilities for the utilization of vehicles of this transport aspect in nonconventional transport technologies. The author discusses the prerequisites of application and development of non-conventional transport technologies with air routes incorporated into the transport chain.